THE NECESSITY OF LIBERALIZATION OF THE REAL ESTATE LEASE AGREEMENT - Tavadyan, Arsen (State and Law, 2022)
The article examines the legislative requirements for the form of lease agreements in the Republic of Armenia. It is noted that the Civil Code of the Republic of Armenia provides for a rather strict approach requiring notarization of any lease agreement concluded with real estate and registration of the rights arising from it in the cadastre.Similar regulations of the CIS and European countries are being studied, where the legislator takes a more liberal approach in the case of short-term lease agreements. Short-term lease agreements are usually concluded in simple written form.The approach taken in the Republic of Armenia unnecessarily restricts civil circulation. As a result, we do not notarize contracts, which deprives the tenant of the opportunity to protect their rights. Landlords can request to vacate the apartment at any time without any restrictions. As a result, the current approach puts vulnerable groups at risk.At the same time, the restriction does not serve any purpose and does not bring a tangible positive effect.Using the methods of economic analysis of law and comparative law, it is substantiated that in the case of a short-term lease of real estate up to one year, notarization of the transaction is not required, and the rights arising from this transaction do not need to be registered. The proposed approach is more logical and aimed at reducing the total costs of participants in civil transactions.At the same time, in the case of unregistered lease agreements, it is proposed to consider them terminated in the event of a change in ownership of the property.
Keywords: lease; state registration; notary verification; form of contract; real estate; property law; obligations law